Dextrin Production by Enzimatic Process from Various Sweet Potatoes in Pontianak - Nana Supriyatna (Biopropal Industri, 2012)
Dextrin is a modified starch that widely used in food and pharmaceutical industries. One of the starch source that could be used for dextrin production is sweet potatoes that widely cultivated in Pontianak. The aims of this study is to produce dextrins enzymatically using different types of sweet potatoes that available in Pontianak. Dextrin production optimization performed on 0.1%, 0.2%, and 0.3% of alpha amylase concentrations and liquification at 95°C for 1, 1.5 and 2 hours. Three varieties of sweet potatoes used: white, yellow, and purple. The results showed that the highest dextrin production is at 0.3% concentration with 2 hours of liquification. The characteristics of the dextrose produced are: fairly soluble in water, dextrose content range 4.14%–4.41%, water content was 10.5% –11.0%, yield range 7%–12%, and 80 mesh filter pass between 91–95%. Dextrins production has met SNI 01-2593-1992 standard dextrin for the food industry.